Secondary cytoreductive surgery - viable treatment option in the management of platinum-sensitive recurrent ovarian cancer. (September 2018) - Felsinger, Michal; Minar, Lubos; Weinberger, Vit; Rovny, Ivo; Zlamal, Filip; Bienertova-Vasku, Julie
Abstract: Objective: This study aimed to evaluate the impact of the secondary cytoreductive surgery on survival parameters in women with platinum-sensitive recurrent ovarian cancer who undergone secondary cytoreduction following chemotherapy compared to women who recieved chemotherapy alone. Study Design: In a retrospective study, data were rewieved from women who were diagnosed and treated with ovarian cancer and its primary platinum-sensitive recurrence at the University Hospital Brno in the Czech Republic between November 2009 and March 2016. Out of the total number of 62 patients with recurrence, 30 women underwent cytoreductive surgery plus chemotherapy and 32 were treated with chemotherapy alone. The good performance status expressed by ECOG score 0–1, the single site of recurrence regardless of platinum-free interval or multiple sites of recurrence but no carcinomatosis and platinum-free interval >12 months, and no or small-volume ascites (<500 ml) were considered inclusion criteria for cytoreductive surgery. Women not meeting these criteria were treated by chemotherapy alone. Descriptive statistics, Kaplan-Meier survival curves and Log-Rank test were used for statistical estimations. Results: The analysis confirmed more favorable prognosis in patient group treated with a combination secondary cytoreduction and chemotherapy. Mean disease-free survival (DFS) was 49.8 months (95% CI; 33.2–66.3) and mean overall survival (OS) stood at 54.0 months (95% CI; 39.4–68.6) in this patient cohort, while in patient group treated with chemotherapy alone it was found that mean DFS was 16.6 months (95% CI; 7.4–25.8) and mean OS stood at 26.2 months (95% CI; 16.6–35.8). When testing the difference between survival curves, statistically significant differences were observed in both DFS (p = 0.010) and OS (p = 0.007) rates between two treatment groups. Age< 60 years at the time of recurrence and zero macroscopic residual disease after secondary cytoreduction were identified as favorable prognostic factors for both DFS and OS in a multivariate analysis. Conclusion: Secondary cytoreductive surgery is acceptable as a viable treatment option for highly selected women with ovarian cancer recurrence. Complete resection is considered ultimate goal of secondary cytoreduction on condition that the balance between maximal survival gain and minimal operative morbidity will be kept.